The effect of the Covid-19 outbreak on the management of acute appendicitis: A retrospective comparative cohort study - Yeşiltaş, Metin (Journal of Surgery and Medicine, 2021)
Background/Aim: Covid-19 pandemic (Cov19) has affected the world since December 2019. The management of acute appendicitis (AA) has also changed distinctly during the Cov19 outbreak. The aim of this study is to evaluate and compare the results of AA during the pre-pandemic period and the first wave of the Cov19 outbreak. Methods: Patients diagnosed with AA from March to July 2019 (pre-pandemic, 2019), and from March to July 2020 (first wave of the pandemic, 2020) were included in this study, and evaluated for age, gender, nationality, length of stay (LOS), ultrasonography (USG), computed tomography (CT) findings, C-reactive protein level (CRP), white blood cell count (WBC), treatment results, operation type, and pathological examination results retrospectively. Results: One hundred patients from 2019, and seventy-seven patients from 2020 were included in the study. The male ratio, false negative USG, number of CTs performed (especially among conservatively treated patients), CRP levels, the rate of conservative treatment were higher, and LOS was longer among patients treated in 2020 (P<0.05 for all). In 2019, 91.8% of the AA operations were performed laparoscopically, whereas in 2020, 73.2% of them were open operations (P<0.001). Complicated AA was more frequent in 2019 than in 2020 (12.2% vs 9.8%). Conclusion: During the Cov19 pandemic, a longer LOS, and a higher ratio of male to female AA patients were observed. CT was more useful during the Cov19 pandemic for diagnosing AA and especially for choosing the suitable patients for conservative treatment. Conservative treatment was preferred more frequently than surgery with a lower recurrence rate in selected uncomplicated patients; and for surgery, the open technique was preferred more frequently during the Cov19 pandemic.